Biochemical and haematological responses to starvation in an air breathing fresh water teleost Heteropneustes fossilis (Bloch) - Borah, Sabita; Yadav, R N S (Indian Journal of Fisheries, 2011)
Lactate dehydrogenase (LDH) activity, amount of protein glucose, glycogenand some haematological parameters of Heteropneustes fossilis (Bloch) wereinvestigated during starvation upto 30 days. The activity of lactatedehydrogenase showed significant decrease as the duration of starvationincreased in both liver and muscles. The amount of protein, glucose andglycogen in the liver and muscle tissues also decreased as the period ofstarvation increased. In contrast the haemoglobin content and total RBCnumber increased during initial period of starvation and thereafter decreasedsignificantly during later period of starvation.